1996
DOI: 10.1101/gr.6.11.1084
|View full text |Cite
|
Sign up to set email alerts
|

Alu fossil relics--distribution and insertion polymorphism.

Abstract: Screening of a human genomic library with an oligonucleotide probe specific for one of the young subfamilies of Alu repeats I~YaS/8] resulted in the identification of several hundred positive clones. Thirty-three of these clones were analyzed in detail by DNA sequencing. Oligonucleotide primers complementary to the unique sequence regions flanking each Alu repeat were used in PCR-based assays to perform phylogenetic analyses, chromosomal localization, and insertion polymorphism analyses within different human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
30
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 39 publications
(50 reference statements)
5
30
0
Order By: Relevance
“…This is important because the presence of an L1 element represents identity by descent, for the probability that two different Ta L1 repeats would integrate independently in the same chromosomal location is negligible. This means that the L1 elements are similar to the previously reported mobile element insertion polymorphisms (Batzer et al , 1994Hammer 1994;Zietkiewicz et al 1994;Arcot et al 1995aArcot et al ,b, 1996Arcot et al , 1998Novick et al 1995;Tishkoff et al 1996;Stoneking et al 1997;Boissinot et al 2000;Jorde et al 2000;Santos et. al.…”
Section: Discussionsupporting
confidence: 70%
“…This is important because the presence of an L1 element represents identity by descent, for the probability that two different Ta L1 repeats would integrate independently in the same chromosomal location is negligible. This means that the L1 elements are similar to the previously reported mobile element insertion polymorphisms (Batzer et al , 1994Hammer 1994;Zietkiewicz et al 1994;Arcot et al 1995aArcot et al ,b, 1996Arcot et al , 1998Novick et al 1995;Tishkoff et al 1996;Stoneking et al 1997;Boissinot et al 2000;Jorde et al 2000;Santos et. al.…”
Section: Discussionsupporting
confidence: 70%
“…phic loci will be biased (Tachida and Iizuka 1993). Random screening of human-specific Alu elements indicates that ∼20% are polymorphic (Arcot et al 1996); hence, we estimate that for the 8 polymorphic loci in our study, we need to include 32 monomorphic loci in the genetic distance calculation. The resulting average genetic distance between African and non-African populations is 0.0246, which from equation 33 of Tachida and Iizuka (1993) corresponds to an effective separation time of 137,000 ‫ע‬ 15,000 years ago.…”
Section: Figurementioning
confidence: 99%
“…Be-cause both the Ya5 and Ya8 Alu subfamilies share a number of diagnostic mutations we refer to this lineage collectively as Ya5/8 . The Ya5/8 Alu subfamily lineage is comprised of 500-2000 elements that are restricted to the human genome (Arcot et al 1996), although a few Ya5 Alu family members have been found in chimpanzees (for review, see Deininger and Batzer 1995). In parallel, a second subfamily that is an independent derivative of the Y lineage of Alu sequences, termed Yb8, has also expanded to ∼500 copies within the human genome (Batzer et al 1995(Batzer et al , 1996a.…”
mentioning
confidence: 99%
“…PCR products were directly visualized using UV fluorescence. The sequences of the oligonucleotide primers, annealing temperatures, PCR product sizes, and chromosomal locations for the loci have been reported previously (Arcot et al 1996(Arcot et al , 1998Stoneking et al 1997). …”
Section: Dna Samples and Alu Genotypingmentioning
confidence: 99%